PELAKSANAAN UPAYA PAKSA PENGEMBALIAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI OLEH KEJAKSAAN TINGGI RIAU - Rezki Saputra Jas; Firdaus '; Erdianto ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
This study aims to: First, review of why a copier certificate of land ownership can not be used as a tool Evidence of criminal report, knowing the constraints Pekanbaru Police investigators conduct investigations case of Land Dispute Riau University; Third, what efforts that done by the University of Riau to solve the problem of land dispute of Riau University. This is a Research sociological, conducted at the Police Resort Kota Pekanbaru, population and sample Was parties, Source Data used is Primary data and secondary data that is document that relate with this case. With Interviews and the study of literature. Results and Discussion concluded that is First, land ownership certificate copy can not be used as a tool Evidence of criminal report because copy of the letter is doesn’t have the strength of evidence; second, the problem that encountered by Pekanbaru Police investigators is the internal factors: lack of facilities and infrastructure of the police and external factors: the lack of means of proof and difficult to call witnesses; Third, efforts What do the Riau University persuasive efforts and report crime.Keywords: Land Dispute Of Riau University - Certificate Of Land Ownership